Electron and photon reconstruction and identification with the CMS experiment at the CERN LHC; Journal of Instrumentation; Vol. 16, iss. 5 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Tyurin N. E. Nikolay Evgenjevich; Babaev A. A. Anton Anatoljevich; Okhotnikov V. V. Vitaly Vladimirovich; Sukhikh L. G. Leonid Grigorievich (2021, 2021)
Title screen